Trans-Beringial Distribution of Platimeliphyllum (Platanaceae) in the Eocene of Eastern Asia and Western North America - Huegele, Indah B.; Zhu, Hai; Zhao, Bailong; Wang, Yu-Fei; Manchester, Steven R. (International Journal of Plant Sciences, 2022)
Premise of research. Our concept of the former diversity and geographic spread of Platanaceae continues to expand. Unlobed platanaceous leaves have been poorly known in the fossil record of western North America. New information on the extinct Paleogene genus Platimeliphyllum and its associated reproductive structures is helping to unravel the biogeographic and evolutionary history of Platanaceae.Methodology. We studied leaves of Platimeliphyllum and associated platanaceous inflorescences and infructescences from the Eocene of western North America and northeastern China. Epidermal anatomy was obtained from cuticle fragments macerated in Schultze solution and studied using transmitted light and epifluorescence microscopy. In situ pollen from inflorescences was studied using light microscopy and SEM.Pivotal results. We provide new evidence supporting the platanaceous affinity of Platimeliphyllum and document its occurrence in the Eocene of western North America as well as in eastern Asia. We present the new combinations Platimeliphyllum durhamensis (Wolfe) comb. nov. from Washington and Oregon and Platimeliphyllum fushunensis (Chen) comb. nov. from Fushun, Liaoning Province, northeastern China. This extends the geographic range of a genus previously known mainly from the Paleocene and Eocene of Russia and Kazakhstan. The ovate, unlobed, simple laminae correspond to Platanaceae in their marginal teeth with rounded sinuses, straight secondary veins, agrophic veins, and orthogonal tertiary and quaternary venation. The association of these leaves with platanaceous inflorescences further confirms their affinities with Platanaceae.Conclusions. Platimeliphyllum likely spread between North America and Asia via the Bering Land Bridge in the Paleocene or Eocene. Previous climate estimates of the Fushun flora based on the coexistence approach need reevaluation with the updated taxonomy of the flora. The co-occurrence of Platimeliphyllum with Macginitiea, Platanites, and Platanus indicates that an array of platanaceous ...